2023
DOI: 10.1126/sciadv.adg6618
|View full text |Cite
|
Sign up to set email alerts
|

Primate-conserved carbonic anhydrase IV and murine-restricted LY6C1 enable blood-brain barrier crossing by engineered viral vectors

Abstract: The blood-brain barrier (BBB) presents a major challenge for delivering large molecules to study and treat the central nervous system. This is due in part to the scarcity of targets known to mediate BBB crossing. To identify novel targets, we leverage a panel of adeno-associated viruses (AAVs) previously identified through mechanism-agnostic directed evolution for improved BBB transcytosis. Screening potential cognate receptors for enhanced BBB crossing, we identify two targets: murine-restricted LY6C1 and wid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 95 publications
0
17
0
Order By: Relevance
“…In addition, pull-down assays demonstrated that P5*-F6*-K7* alone are sufficient for binding to Ly6A in vitro and constitute the minimal motif for this interaction. In agreement, a newly developed integrative structure computational modeling pipeline used to model the AAV-PHP.eB–Ly6A interaction pointed at P5*-F6* as being essential for binding, showing that Ly6A interacts with one capsid monomer and that additional interactions induce steric clashes [ 259 ].…”
Section: Mechanistic Insight For the Transduction Of Novel Aav Capsid...mentioning
confidence: 91%
See 3 more Smart Citations
“…In addition, pull-down assays demonstrated that P5*-F6*-K7* alone are sufficient for binding to Ly6A in vitro and constitute the minimal motif for this interaction. In agreement, a newly developed integrative structure computational modeling pipeline used to model the AAV-PHP.eB–Ly6A interaction pointed at P5*-F6* as being essential for binding, showing that Ly6A interacts with one capsid monomer and that additional interactions induce steric clashes [ 259 ].…”
Section: Mechanistic Insight For the Transduction Of Novel Aav Capsid...mentioning
confidence: 91%
“…After intracranial injection in rat or mice, it transduced preferentially NSCs with a higher efficiency than the parental serotype [ 258 ]. Finally, a recent study engineered AAV-PHP.eC , a novel variant derived from AAV-PHP.C1 which outperformed AAV-PHP.C2 in CNS targeting in multiple mouse strains after IV delivery, transducing neurons and astrocytes [ 259 ].…”
Section: Novel Aav Variants For Targeted Tropismmentioning
confidence: 99%
See 2 more Smart Citations
“…As compared to natural AAV capsids such as AAV9 and AAV2 that are used in approved gene therapies, BI-hTFR1 demonstrated the remarkable ability to be actively transported across a human brain endothelial cell layer and to cross the BBB and transduce cells throughout the brains and spinal cords of TFRC KI mice after intravenous delivery. BI-hTFR1 exhibited a broad CNS tropism enhancement similar to those observed with engineered mouse BBB-crossing capsids, e.g., AAV-PHP.B, BI28, AAVF, and 9P31 that bind to mouse GPIanchored proteins LY6A, LY6C1, or Car4 (25,59,60). By engaging highly abundant CNS endothelial cell surface proteins as new receptors, these capsids are able to efficiently cross the BBB and gain access to parenchymal cells.…”
Section: Discussionmentioning
confidence: 78%